Rural Womens’ Access to Community Finance - Kharel, Suman (Nepalese Journal of Development and Rural Studies, 2017)
This study explained access of women in community finance and its impact on their household economy. To the end, 140 community finance groups of Phulwari Village was regarded as case of the study and purposively selected 66 households were unit of analysis. Under case study methodology, descriptive/explanatory research design was used to analyze collected data. The study found that out of total 140 community finance groups, 92 were women led, 6 men led and 42 were jointly led by men and women. And from 66 sample households women are involved in 154 financial groups. The numbers of members in one financial group ranges from 9 to 296 at the time of establishment. A total amount NRs 22 million is saved from financial groups. The natures of groups are mostly unregistered, led by women, small amount of saving and dominated by Brahmin and Chhetri. Community finance has increased saving habit of the members and led them more access to credit facilities. Women are socio-economically and politically empowered due to the impact of community finance. They are participating in community work, becoming self-employed and supported to household economy. The status of the family has been improved. Finally, the study found that, level of education, labour migration, saving/credit and training opportunities are the motivational factors for involving women in community finance. Nepalese Journal of Development and Rural Studies Vol. 14 (Joint issue) (1&2), 2017, Page: 112-123